Characterizing the Microbial Consortium L1 Capable of Efficiently Degrading Chlorimuron-Ethyl via Metagenome Combining 16S rDNA Sequencing - Li, Xiang; Lu, Changming; Dai, Yumeng; Yu, Zhixiong; Gu, Wu; Li, Tingting; Li, Xinyu; Li, Xu; Wang, Xiujuan; Su, Zhencheng; Xu, Mingkai; Zhang, Huiwen (Frontiers in Microbiology, 2022)
Excessive application of the herbicide chlorimuron-ethyl severely harms subsequent crops and poses severe risks to environmental health. Therefore, methods for efficiently decreasing and eliminating chlorimuron-ethyl residues are urgently needed. Microbial consortia show potential for bioremediation because of their strong metabolic complementarity and synthesis. In this study, a microbial consortium entitled L1 was enriched from soil contaminated with chlorimuron-ethyl by “top-down" synthetic biology strategy. The consortium could degrade 98.04% of 100 mg L-1 chlorimuron-ethyl within six days. We characterized it from the samples at four time points during the degradation process and a sample without degradation activity via metagenome and 16S rDNA sequencing. The results revealed 39 genera in consortium L1, among which Methyloversatilis (34.31%), Starkeya (28.60%), and Pseudoxanthomonas (7.01%) showed relatively high abundances. Temporal succession and the loss of degradability did not alter the diversity and community composition of L1 but changed the community structure. Taxon-functional contribution analysis predicted that glutathione transferase [EC 2.5.1.18], urease [EC 3.5.1.5], and allophanate hydrolase [EC 3.5.1.54] are relevant for the degradation of chlorimuron-ethyl and that Methyloversatilis, Pseudoxanthomonas, Methylopila, Hyphomicrobium, Stenotrophomonas, and Sphingomonas were the main degrading genera. The degradation pathway of chlorimuron-ethyl by L1 may involve cleavage of the chlorimuron-ethyl carbamide bridge to produce 2-amino-4-chloro-6-methoxypyrimidine and ethyl o-sulfonamide benzoate. The results of network analysis indicated close interactions, cross-feeding, and co-metabolic relationships between strains in the consortium, and most of the above six degrading genera were keystone taxa in the network. Additionally, the degradation of chlorimuron-ethyl by L1 required not only "functional bacteria" with degradation capacity, but also "auxiliary bacteria" without degradation capacity but that indirectly facilitate/inhibit the degradation process; however, the abundance of "auxiliary bacteria" should be controlled in an appropriate range. These findings improve the understanding of the synergistic effects of degrading bacterial consortia, which will provide insight for isolating degrading bacterial resources and constructing artificial efficient bacterial consortia. Furthermore, our results provide a new route for pollution control and biodegradation of sulfonylurea herbicides.